ANTITRANSPIRANTS APPLICATION FOR IMPROVING THE BIOCHEMICAL CHANGES OF BARLEY UNDER WATER STRESS - & et al., Hellal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Field experiment carried out at Nubaria Agricultural Research station, National Research Centre, Egypt to study the role of antitranspirants applicationSalicylic Acid (SA), K2SO4 and MgCO3 in alleviating drought-induced changes of some sensitive barley varieties. Foliar application of the antitranspirants compounds registered a positive effect on plant pigment, relative water content, nutrient contents and proline accumulation under water stress condition especially after spraying SA. The barley varieties Tamellalet and Giza 125 highly responded to antitranspirants application especially after foliar application of SA and MgCO3 over remaining varieties. Application of MgCO3 produced the most balanced nutrients for Tamellalet variety under normal irrigation system whereas, under stress condition. The data together provide some indication that Ksar-Megrine and Tombari cultivars has more efficient H2O2 scavenging machinery at least in peroxisomes under drought stress. Application of antitranspirants treatments led to significant increase of CAT, POD and GR activity which could alleviate the adverse effect of water stress on barley leaves. Results concluded that antitranspirants application could be effective for barley production in arid and semi-arid areas to reduce the adverse effects of water deficit.